Cuffing‐based photoacoustic flowmetry in humans in the optical diffusive regime. Issue 3 (30th October 2015) - Zhou, Yong; Liang, Jinyang; Wang, Lihong V.
Abstract : Measuring blood flow speed in the optical diffusive regime in humans has been a long standing challenge for photoacoustic tomography. In this work, we proposed a cuffing‐based method to quantify blood flow speed in humans with a handheld photoacoustic probe. By cuffing and releasing the blood vessel, we can measure the blood flow speed downstream. In phantom experiments, we demonstrated that the minimum and maximum measurable flow speeds were 0.035 mm/s and 42 mm/s, respectively. In human experiments, flow speeds were measured in three different blood vessels: a radial artery in the right forearm, a radial artery in the index finger of the right hand, and a radial vein in the right forearm. Taking advantage of the handheld probe, our method can potentially be used to monitor blood flow speed in the clinic and at the bedside. Abstract : Measuring blood flow speed in the optical diffusive regime in humans has been a long standing challenge for photoacoustic tomography. A cuffing‐based method to quantify blood flow speed in humans with a handheld photoacoustic probe is proposed. By cuffing and releasing the blood vessel, the blood flow speed downstream can be measured. Taking advantage of the handheld probe, the method can potentially be used to monitor blood flow speed in the clinic and at the bedside.